TTF-1 Positive Primary Small Cell Carcinoma of the Breast: A Case Report and Review of the Literature - Boutrid, Hinda; Kassem, Mahmoud; Tozbikian, Gary; Morgan, Evan; White, Julia; Shah, Manisha; Vandeusen, Jeffrey; Sardesai, Sagar; Williams, Nicole; Stover, Daniel G.; Lustberg, Maryam; Wesolowski, Robert; et al. (Frontiers in Endocrinology, 2020)
Primary small cell carcinoma of the breast (SCCB) is a rare tumor subtype comprising less than 0.1% of all breast carcinomas. Here we present a case of thyroid transcription factor-1 (TTF-1) positive SCCB that recurred within three years of diagnosis in the lung and lymph nodes. Given the small number of cases, no clear guidelines exist on the appropriate management of patients with these aggressive tumors. We present a case study and review the current literature to highlight the knowledge gaps and needs of patients with these rare tumors. A 50-year-old premenopausal woman with no family history, presented with a palpable right breast mass. The biopsy was consistent with primary SCCB that was poorly differentiated, positive for synaptophysin and chromogranin and TTF-1 and presence of ductal carcinoma in situ component showing neuroendocrine differentiation. Imaging with PET, CT, and MRI brain excluded any other sites of the primary disease. She underwent a right lumpectomy with axillary lymph node dissection and was treated with adjuvant cisplatin-based chemotherapy and concurrent radiation therapy. Thirty-four months later, routine scans showed a new right lower-lobe lung nodule and an enlarged sub-carinal node that was proven to be poorly differentiated neuroendocrine cancer. This case report sheds light on a rarely described disease and provides a comprehensive approach to diagnosis and management. Primary SCCB is an extremely rare, aggressive form of breast carcinoma that is molecularly and histologically similar to SCLC. However, a review of the literature highlights recent mutational analyses that show important differences between these two cancer types, including an increase in PIK3CA mutations in primary SCCB. Further studies, including genomic analyses, are needed to better define this malignancy and to develop a standard treatment.